Associations of Socioeconomic Status With Disease Progression in African Americans With Early Rheumatoid Arthritis. Issue 1 (6th September 2022) - Astrike‐Davis, Emma M.; Cleveland, Rebecca J.; Louis Bridges, S.; Jonas, Beth L.; Callahan, Leigh F.
Abstract : Objective: In prior cross‐sectional analyses of African American patients with rheumatoid arthritis (RA), measures of socioeconomic status (SES) were associated with clinical joint damage and poorer patient‐reported outcome scores. The purpose of this study was to determine whether SES measures are associated with disease progression in a cohort of African American patients with early RA (<2 years duration). Methods: We analyzed baseline SES and change in 60‐month clinical radiographs and patient‐reported outcomes data (n = 101 and 177, respectively) in individuals with early RA. SES measures were educational attainment, occupation, homeownership, household income, and block group poverty. Outcomes were based on radiographs (total erosion and joint space narrowing [JSN] scores on hands and feet) and patient‐reported outcomes (pain, fatigue, disability, and learned helplessness). We used logistic regression with mixed effects accounting for study site to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: Both low education and occupation status were associated with worsening pain (adjusted OR 5.86 [95% CI 3.05–11.3] and adjusted OR 2.55 [95% CI 1.54–4.21], respectively). Patients without a high‐school diploma were more likely to have worsened reports of learned helplessness (OR 1.92 [95% CI 1.37–2.67]). Community measures of SES were also significantly associated with patient‐reported outcomes score changes. Patients living in areas of block group poverty ≥20% were twice as likely to experience increased disability scores over 60 months of disease duration (OR 1.95 [95% CI 1.17–3.25]). We found no association between SES measures and erosion or JSN score progression. Conclusion: Low educational attainment and nonprofessional occupation status were associated with increased worsening of patient‐reported outcomes. However, there were no corresponding increases in radiographically assessed erosion or JSN score progression.